Döda kroppar och döda ting : Materialitet och affekt i museiutställningar med mänskliga kvarlevor och artefakter. - Åkebrand,Miriam (2026)
This thesis examines how museums display human remains in relation to artefacts within the same exhibition contexts. While previous research has largely focused on ethical questions, repatriation, and public reactions to human remains, fewer studies have systematically compared how museums materially and affectively differentiate human remains from other museum objects. The study investigates three museums with different institutional backgrounds: Medical Museion in Copenhagen, the Museum of Evolution in Uppsala, and Gothenburg City Museum. Through a qualitative and comparative exhibition analysis inspired by David Whitehead’s walkthrough methodology, the thesis analyses how human remains and artefacts are presented through spatial design, display techniques, narrative framing, and affective atmosphere.The theoretical framework combines material culture theory and affect theory. Material culture theory is used to analyse how objects are assigned cultural and symbolic value, while affect theory provides tools for understanding how exhibitions produce emotional and sensory responses. The findings demonstrate that human remains are consistently treated differently from artefacts. Museums frequently use strategies such as isolated placement, subdued lighting, warning signs, ethical contextualisation, and individualising narratives to frame human remains as morally and emotionally sensitive objects. Artefacts, by contrast, are more often presented primarily as historical or scientific material. The study also shows that exhibition design strongly shapes affective responses such as discomfort, empathy, fascination, and reflection. The thesis argues that museums construct human remains as objects with a distinct ontological and ethical status. Through exhibition practices, museums actively shape how visitors understand, emotionally respond to, and assign value to human remains in comparison to artefacts. The study contributes to museological research on materiality, affect, and the ethics of display.
Keywords: museum studies; human remains; materiality; affect; exhibition analysis; museum display; ethics; artefacts.